Information Systems Quality and Corporate Sustainability: Unpacking the Interplay of Financial Reporting, Artificial Intelligence, and Green Corporate Governance - Nidal Neiroukh; Dilber Çağlar (Systems)
This study explores how the quality of information systems quality in management accounting (ISQMA) is associated with corporate sustainability (CS), focusing on the role of financial reporting accuracy and contextual enablers such as artificial intelligence (AI) and green corporate governance (GCG). Drawing on the Resource-Based View and Contingency Theory, the study investigates whether accurate financial data reporting (AFDR) functions as a mechanism through which ISQMA contributes to sustainability outcomes, and whether the presence of AI and GCG strengthens these associations. Empirical data were collected from 257 accounting and finance professionals working in Jordanian commercial banks, providing a robust setting where digital infrastructure and sustainability imperatives converge. The results reveal that ISQMA is positively associated with both AFDR and CS, with AFDR partially mediating this relationship. Moreover, AI and GCG were found to strengthen the relationships between ISQMA and AFDR, and between ISQMA and CS, respectively. These findings underscore that accurate, reliable financial reporting, and strong governance practices enhance the value of digital information systems in achieving corporate sustainability objectives. By integrating information quality, technological capabilities, and governance mechanisms, this study offers a comprehensive understanding of how banks can align their digital infrastructure with sustainable performance goals. The insights contribute to the growing discourse on digitally enabled sustainability and offer actionable implications for both practitioners and policymakers in emerging markets.